Global research trends on cardiac troponin and physical activity among pediatric populations: a bibliometric analysis and science mapping study - Hernández-González, Vicenç; Conesa-Milian, Enric; Jové-Deltell, Carme; Pano-Rodríguez, Álvaro; Legaz-Arrese, Alejandro; Reverter-Masia, Joaquin (Frontiers in Pediatrics, 2024)
Background Cardiac troponin (cTn) is a reliable marker for evaluating myocardial damage. cTn is a very specific protein involved in myocardial injury, and it is a key factor in the diagnosis of coronary syndromes. Bibliometric analysis was applied in the present work, with the main goal of evaluating global research on the topic of cardiac troponin in pediatric populations. Methods Publications about cardiac troponin and physical activity in pediatric populations were retrieved from the Social Sciences Citation Index (SSCI) and the Science Citation Index Expanded (SCIE) of the Web of Science Core Collection, and they were then analyzed. The study was able to identify the key bibliometric indicators, such as publications, keywords, authors, countries, institutions, and journals. For the analysis, VOSviewer, R-based Bibliometrix (4.2.2), and MapChart were used. Results Initially, 98 documents were identified; however, once inclusion and exclusion criteria were applied, the number of documents decreased to 88. The search yielded 79 original research articles and 9 reviews, almost all of which were published in the past 2 decades. The total number of citations (Nc) of the retrieved publications was 1,468, and the average number of citations per article (Na) was 16.68. In general, 508 authors were found to have participated in research about troponin; they were associated with 256 institutions, and their work was published in 65 different journals from around the world. The authors hailed from 30 countries and/or regions. The year 2022 was the most productive year for the publication of the selected documents. The bibliometric analysis provided information regarding levels of cooperation among authors and institutions. In fact, China, the United States, and England were the most productive nations, and the journal with the greatest number of publications on the topic was Pediatric Cardiology. Summary The number of publications and the trend line show that research on this topic has not yet reached a stage of maturity. There are referent investigators, countries, and institutions that have laid the foundations for subsequent studies on the analyzed topic.